PENERAPAN MODEL PEMBELAJARAN NUMBERED HEADS TOGETHER (NHT) DAN MODEL PEMBELAJARAN GROUP INVESTIGATION (GI) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS XI IPA SMAN 5 KUPANG - Naikteas.Bano, Natalia.D.; Supu, Amiruddin; Lantik, Vinsensius (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2019)
The purpose of this study was to determine the difference in students ' critical thinking skills taught using the learning models of Numbered Heads Together and Group Investigation. This research was an experimental research with the design of randomized control group pre-Test post-Test design. Research conducted in class XI IPA SMA Negeri 5 Kupang. Data analysis was conducted using test-T. T test result with a significant level of 5% (Î± = 0.05) obtained the value of Sig (2-tailed) 0,006<0,05 so Ha accepted. It indicates that there are significant differences in critical thinking skills between students taught using Numbered Heads Together and Group Investigation learning models. The critical thinking ability of students taught using the Numbered Heads Together learning model is higher than the students taught using the Group Investigation learning model.